2017
DOI: 10.1161/circulationaha.117.028388
|View full text |Cite
|
Sign up to set email alerts
|

A Novel α-Calcitonin Gene-Related Peptide Analogue Protects Against End-Organ Damage in Experimental Hypertension, Cardiac Hypertrophy, and Heart Failure

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
79
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 50 publications
3
79
0
Order By: Relevance
“…Our results from the in vivo experiments confirmed that chronic (14 days) Ang II exposure resulted in left ventricular hypertrophy (as assessed by WGA and H&E staining) and decreased EF and FS. Aubdool et al (2017) indicated that continuously infused Ang II (1.5 mg·kg −1 ·day −1 ) for 14 days via osmotic mini pumps could induce hypertension, cardiac hypertrophy, and hypertensive HF in mice. In the present study, we did not measure the changes of BP in animals due to our focus on the hypertensive HF.…”
Section: Discussionmentioning
confidence: 99%
“…Our results from the in vivo experiments confirmed that chronic (14 days) Ang II exposure resulted in left ventricular hypertrophy (as assessed by WGA and H&E staining) and decreased EF and FS. Aubdool et al (2017) indicated that continuously infused Ang II (1.5 mg·kg −1 ·day −1 ) for 14 days via osmotic mini pumps could induce hypertension, cardiac hypertrophy, and hypertensive HF in mice. In the present study, we did not measure the changes of BP in animals due to our focus on the hypertensive HF.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in an animal model of Ang II‐induced hypertension, RAMP1 transgenic mice were shown to be protected from increases in their SBP 24 . However, the CGRP and/or CGRP receptor expression profile varies with the state and stage of the disease, including that in the Ang II‐induced model 25,26 . In addition, the change in CGRP receptor expression was suggested to further amplify the responses to CGRP, especially in the hypertension model 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation and oxidative stress together contribute to cardiac cell dysfunction and apoptosis . Therefore, we have investigated the effects of 6b on cell morphology and apoptosis in hyperglycaemia‐induced in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%